On the autumn food of Barnacle Geese at Caerlaverock National Nature Reserve - Owen, Myrfyn; Kerbes, R H (Wildfowl, 1971)
An analysis of droppings of Barnacle Geese Branta leucopsis was made to identify the food of those birds on a wintering area of the Solway Firth in 1970. Their diet consisted of 44% seed, mainly of Juncus gerardii, mud rush; 14% Trifolium repens, clover, stolons, and 42% grass and other leaf material. Barnacle Geese are flexible in their feeding behavior, and their ability to use seeds and stolons, which have much higher energy value than grass, probably allows them to lay down fat before the onset of winter. There are indications that the geese select sea poa grass Puccinellia maritima in preference to red fescue Festuca rubra from the merse sward. The technique of faecal analysis as applied to geese is briefly discussed, and it is concluded that the method used here is a promising one for use in feeding studies on wildfowl.